The Effectiveness of an Interactive Flipbook on Nutrition Knowledge in Mandailing Culinary on Students Ability to Plan a Balanced Menu Using Local Foods Ingredients - Emilia, Esi; Pratiwi, Caca; Haryana, Nila Reswari (Journal of Ecohumanism, 2024)
This study examines the effects of an interactive flipbook on nutrition knowledge in Mandailing cooking schools and how it affects students’ capacity to plan a balanced dinner utilizing local food ingredients. A quantitative quasi-experimental approach was used, with 101 nutrition students divided into two groups: an experimental group (49 students) using the flipbook and a control group (52 students) using the e-book. Pre- and post-tests were used to evaluate the students’ baseline and post-intervention knowledge and abilities. Both groups saw a 3-point increase in average scores, but there was a significant difference (Asymp. Sig value of 0.001 < 0.05) in post-test results, indicating that the flipbook had a greater impact on learning outcomes than the e-book. Furthermore, 60.5% of the students indicated the flipbook was very engaging and interesting, especially when it came to creating a balanced menu utilizing local Mandailing food, while 39.5% thought it was good. Most students appreciated the inclusion of specific nutritional content, which helped them understand local foods and calculate dietary values for balanced menu planning. These findings indicate that the interactive flipbook is useful for increasing participation and nutrition knowledge in Mandailing culinary education.